Symbolic Meaning in Tradition The Malem Selikuran of Keraton Kasunanan Surakarta Hadiningrat, Indonesia - Moh Sayful Zuhri; Ivan Prapanca Wardhana (Universitas Sebelas Maret, 2024)
Culture in Indonesia is very diverse, including Javanese culture. This culture developed through the acculturation process that occurred in Javanese society. Each culture has its own meaning or symbolism which is usually connected between humans and God. The Malem Selikuran di Keraton Kasunanan Surakarta Hadiningrat tradition has quite a broad meaning. This tradition is not only a celebration, but also has meaning contained in it, for example a means to strengthen a Muslim's faith, strengthen ties of brotherhood, and preserve culture. In today's life, it is important to maintain unity, respect existing diversity, and to always be grateful for the blessings that God has given. This research is qualitative research with an ethnographic approach. This approach is used because the ethnographic approach focuses on sociological meaning through field observations of sociocultural phenomena, so that the data obtained is quite clear. The results of this research are in the form of symbolic meaning contained in the traditional activities of the Malem Selikuran in the Keraton Kasunanan Surakarta Hadiningrat.